Environmental social sciences : methods and research design. - Vaccaro, Ismael; Smith, Eric Alden; Aswani, Shankar (Cambridge University Press, 2010)
"The relationship between human communities and the environment is extremely complex. In order to resolve the issues involved with this relationship, interdisciplinary research combining natural sciences, social sciences, and humanities is necessary. Here, specialists summarise methods and research strategies for various aspects of social research devoted to environmental issues. Each chapter is illustrated with ethnographic and environmental examples, ranging from Australia to Amazonia, from Madagascar to the United States, and from prehistoric and historic cases to contemporary rural and urban ones. It deals with climate change, deforestation, environmental knowledge, natural reserves, politics and ownership of natural resources, and the effect of differing spatial and temporal scales. Contributing to the intellectual project of interdisciplinary environmental social science, this book shows the possibilities social science can provide to environmental studies and to larger global problems and thus will be of equal interest to social and natural scientists and policy makers" -- Présentation de l'éditeur.